A novel approach for improvement of purity and porosity in diatomite (diatomaceous earth) by applying an electric field - Jung, Kyung-Won; Jang, Duksoo; Ahn, Kyu-Hong (ELSEVIER, 2014)
In this study, a novel and a facile purification approach using an electric field was developed to improve the porous structure of raw diatomite by removal of impurities from its surface and clogged pores. Voltages of 50 and 100 V were applied for 30 min, and the feasibility and efficiency of this approach were determined by comparison of the properties of the product with those of raw diatomite. The chemical, physical, and microstructural results confirmed that the electric field successfully improved the porosity, specific surface area, and enhanced absorptive efficiency of diatomite. The results suggest that application of an electric field has reasonable potential as an alternative method for improving diatomite quality. This is the first report documenting the successful improvement of diatomite using an electric field. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: PURIFICATION